Relative expression of receptors in uterine natural killer cells compared to peripheral blood natural killer cells - Ismail, Nurul Izza (Frontiers in Immunology, 2023)
One would expect maternal immune cells to attack the invading trophoblast as the placenta is semi-allogenic. However, they appear to cooperate with the trophoblast in disrupting the arterial wall which has been determined in several studies. uNK cells are a particular type of immune cell that appears to play a role in pregnancy. As in pregnancy, the key contributors to trophoblast invasion appear to be a unique combination of genes, which appear to regulate multiple components of the interactions between placental and maternal cells, called HLA class 1b genes. The HLA class 1b genes have few alleles, which makes them unlikely to be recognized as foreign by the maternal cells. The low polymorphic properties of these particular HLAs may aid trophoblasts in actively avoiding immune attacks. This review gives a complete description of the mechanisms of interaction between HLAs and maternal uNK cells in humans.